MANAGEMENT PRACTICES OF ADVERSE REACTIONS RELATED TO ANESTHESIA USE AMONG EYE SURGERY PATIENTS IN JINJA REGIONAL REFERRAL HOSPITAL, JINJA, UGANDA. A CROSS-SECTIONAL STUDY. - MASAYI , MASABA STEVEN; KITANDA , JONATHAN (Student’s Journal of Health Research Africa, 2024)
Background. Uganda, like any other developing country, bears a heavy burden of eye disease which contributes significantly to visual problems. Increasing eye surgeries, therefore, demands analyzing anesthetics to enhance patient safety. This study aimed to determine the management practices of adverse reactions related to anesthesia use among eye surgery patients in Jinja Regional Referral Hospital, Jinja, Uganda. Methodology. The study used a descriptive cross-sectional design and quantitative data were collected from 72 patients. A simple random sampling technique was used to pick respondents and pre-tested structured questionnaires were formulated and used to collect data. Results. (42%) of the patients had previous history of eye surgery, 75% of patients recovered within the first hour. (70%) of healthcare providers primarily managed adverse anesthetic reactions using medication, Oxygen therapy (14%) was used to stabilize patients with respiratory distress, vital sign monitoring (16%) ensured patient safety by tracking key indicators. Patient education (11%) helped reduce anxiety by preparing patients for potential side effects. In cases of excessive sedation, reversal agents (8%) like flumazenil were used to awaken patients. Conclusion. Management of anesthesia-related side effects primarily relied on medication and postoperative monitoring. While these strategies were largely effective, there is room for improvement in managing severe pain, reducing side effects, and enhancing patient education before surgery. Recommendation. Ensure careful titration of sedatives and monitor sedation levels closely during surgery. Increase the use of reversal agents in cases of excessive sedation to promote quicker recovery and minimize postoperative complications.